The Practices Of Sustainability Factors And Perceived Sustainable Construction Firms’ Performance Among Contractors In Malaysia - Rashideh, Waleed Mohamad Abdo (2010)
Sustainability consists of three main pillars, namely: environmental, economic and social pillars. Its major thrust is an attempt to balance the use of resources between the present and future generations. As one of the major contributors to the global and local environmental problems, the construction industry is hard pressed to streamline its processes while executing projects. In the context of the Malaysian construction industry, there is a need for sustainability assessment framework that will integrate environmental, economic and social factors. This framework should answer a multitude of problems in achieving a higher degree of sustainability in the industry.